Analisis Pengaruh Promosi Jabatan dan Disiplin Kerja Terhadap Kinerja Pegawai BPN Kota Bekasi (Mulia Pratama, 2022)
The Bekasi City BPN Office is a government agency engaged in the land sector. Which serves the registration process for land certificates, specifically for the Bekasi City area. The Bekasi City BPN office is located at Jl. Chairil Anwar No.25. In this study, it will only be limited to HUMAN RESOURCES, especially PPNPN, Bekasi City BPN Office. With the emergence of problems regarding aspects of Job Promotion and Work Discipline on Employee Performance. Problems with information regarding promotions, periodization of promotions, relatively heavy requirements, not yet optimally applicable sanctions, unequal justice, and not yet optimal appreciation for employees who work according to targets. Researched using a questionnaire distribution system with 50 responses. The results of the questionnaires that have been collected are then obtained through the SPSS version 26 application. The effect of Job Promotion and Work Discipline on Employee Performance is 34.1%. Partially the effect of the Job Promotion variable (X1) on Employee Performance (Y) is 26.3%. Partially the effect of work discipline variable (X2) on employee performance (Y) is 33.0%. Based on the results of data processing regarding the effect of Job Promotion and Work Discipline on Employee Performance, it should be further optimized again. Steps that can be taken in optimizing employee performance can be to increase training on a regular basis, provide motivation in the form of rewards, and increase the level of leadership leadership. Thus, it is expected that employee performance can run more optimally.